HOW CONVENTIONS MAKE VISUALISATIONS (AND THEIR DATA) SEEM OBJECTIVE - Kennedy, Helen; Hill, Rosemary Lucy (AoIR Selected Papers of Internet Research, 2015)
This paper highlights the work that conventions do in making visualisations seem objective. This focus on visualisation conventions is important in order to make sense of the apparent contradiction between critics’ assertions that visualisations serve as mechanisms of control and designers’ assertions of their desire to ‘do good with data’ (Periscopic, nd). We focus on two conventions here. First, the use two-dimensional viewpoints, such as front-on views in graphs or top-down views in maps and pie charts, which encode objectivity because the ’distortions that usually come with perspective’ are ’neutralised’ (2006, p.149). Second, the inclusion of data sources in visualisations, which call upon the viewer to see visualisations as objective and based on ‘facts’. Thus designers make choices about the data visualisations that they produce, but their choices are constrained by semiotic resources and other conventions that are available to them. We argue that visualisers are not in league with ‘them’ to bamboozle ‘us’, as one participant in our focus groups with visualisation consumers claimed. Rather, they do their best to ‘do good with data’ with available conventions. Thinking in this way advances understanding of the ways in which visualisations come into being, the conventions on which visualisers draw to produce them, and how these conventions imbue visualisations with particular qualities.